Analysis of G-Quadruplex-Forming Sequences in Drought Stress-Responsive Genes, and Synthesis Genes of Phenolic Compounds in Arabidopsis thaliana - Pečinka, Petr; Bohálová, Natália; Volná, Adriana; Kundrátová, Kristýna; Brázda, Václav; Bartas, Martin (Life (Basel, Switzerland), 2023)
Sequences of nucleic acids with the potential to form four-stranded G-quadruplex structures are intensively studied mainly in the context of human diseases, pathogens, or extremophile organisms; nonetheless, the knowledge about their occurrence and putative role in plants is still limited. This work is focused on G-quadruplex-forming sites in two gene sets of interest: drought stress-responsive genes, and genes related to the production/biosynthesis of phenolic compounds in the model plant organism Arabidopsis thaliana. In addition, 20 housekeeping genes were analyzed as well, where the constitutive gene expression was expected (with no need for precise regulation depending on internal or external factors). The results have shown that none of the tested gene sets differed significantly in the content of G-quadruplex-forming sites, however, the highest frequency of G-quadruplex-forming sites was found in the 5'-UTR regions of phenolic compounds' biosynthesis genes, which indicates the possibility of their regulation at the mRNA level. In addition, mainly within the introns and 1000 bp flanks downstream gene regions, G-quadruplex-forming sites were highly underrepresented. Finally, cluster analysis allowed us to observe similarities between particular genes in terms of their PQS characteristics. We believe that the original approach used in this study may become useful for further and more comprehensive bioinformatic studies in the field of G-quadruplex genomics.
Keywords: phenolic compounds; PQS; G-quadruplex; drought stress; Arabidopsis thaliana